Ethnomedicine: Applications of Neem (Azadirachta indica) in dentistry - Atul Kaushik; Renu Tanwar; Monika Kaushik (Wolters Kluwer Medknow Publications, 2012)
Ethnomedicine is the study of traditional medicines having relevant written sources (Ayurveda, traditional Chinese Medicine) as well as those whose knowledge and practices have been orally transmitted over the centuries. The Neem tree (Azadirachta indica) has been known as the wonder tree for centuries in the Indian subcontinent. It has become important in the global context today because it offers solutions to the multiple concerns faced by mankind. Each part of the Neem tree has some medicinal property and the broad range of biologic activities and pharmacologic actions of Neem tree are very well established. Although literature search reveals that Neem tree has multiple potential uses in dentistry, its application is limited in routine dental practice. The following manuscript is an attempt to throw light on the potential and immense uses of Neem tree products for oral care, which forms a critical issue in both developing countries where professional dental care is limited and in developed nations where populations are aging.